2020
DOI: 10.1126/science.abb6144
|View full text |Cite
|
Sign up to set email alerts
|

Which interventions work best in a pandemic?

Abstract: Circles on the grounds of San Francisco's Dolores Park are designed to limit the spread of SARS-CoV-2 by encouraging social distancing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
134
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(140 citation statements)
references
References 14 publications
3
134
0
3
Order By: Relevance
“…Non-pharmaceutical interventions (e.g., social distancing, hand washing, universal masking) are the only measures currently available to limit the spread of COVID-19 [34], while contact tracing and isolation have been implemented to contain infected individuals [35]. Simulation results [35] showed that a COVID-19 outbreak can be controlled within 3 months if such strategies are put in place rapidly and effectively.…”
Section: Sub-national Dynamics and Interventionsmentioning
confidence: 99%
“…Non-pharmaceutical interventions (e.g., social distancing, hand washing, universal masking) are the only measures currently available to limit the spread of COVID-19 [34], while contact tracing and isolation have been implemented to contain infected individuals [35]. Simulation results [35] showed that a COVID-19 outbreak can be controlled within 3 months if such strategies are put in place rapidly and effectively.…”
Section: Sub-national Dynamics and Interventionsmentioning
confidence: 99%
“…Os resultados da intervenção, por ora apresentados, comungam com diversos estudos preventivos sobre o aumento de transmissĂŁo da COVID-19, a exemplo disso, as intervençÔes nĂŁo farmacolĂłgicas, das quais constam medidas comportamentais (Haushofer & Metcalf, 2020), como higienizar as mĂŁos, principalmente ao tossir e espirrar, fazer o uso de mĂĄscaras e evitar aglomeraçÔes (Silva et al, 2020;Sales et al, 2020), açÔes que tĂȘm maior possibilidade de transmissibilidade.…”
Section: Discussionunclassified
“…We assumed a price per test from $1200 to $7500 mxn-from $53 to $332 usd 27 . Finally, we use the randomized controlled trails (RCTs) approximation in our model to show its importance and practical implementation in local indoor environments for reducing the virus transmission 28 . For example, different sizes of workplaces, based on the number of workers indoors, can randomly choose individuals and keep track of their testing results and contact tracing to monitor data.…”
Section: Methodsmentioning
confidence: 99%